Building a proposed counseling program based on social theory to improve some life skills among middle school students (Journal of the College of Basic Education, 2023)
Relations with (The skill of effective communication and building people), and the second domain includes (the skill of self-awareness and empathy), and the third domain includes (the skill of managing emotions and facing pressures), and after extracting the psychometric properties of the scale, a counseling program was built according to the Bords and Dardi model, including (12) a suggested counseling session to improve some skills The life of middle school students based on the techniques of Bandura’s social theory and extracted the apparent honesty of the program after presenting it to a group of arbitrators specialized in psychological counseling and educational guidance